(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge and practices regarding occupational radiation exposure prevention among medical imaging students, and to identify factors associated with their knowledge and practices. Method: A cross-sectional study was conducted on 107 second-, third-, and fourth-year medical imaging students at Pham Ngoc Thach University of Medicine. Results: The proportion of students demonstrating good knowledge and practice in preventing occupational radiation exposure was 57.94%, while 42.06% still lacked adequate knowledge and practical skills. No statistically significant associations were found between general demographic characteristics and students’ knowledge and practices related to radiation protection. Conclusion: The proportion of students with good knowledge and practice indicates that more than half possess a reasonable understanding and the ability to apply principles of occupational radiation protection. However, nearly half still show limitations, highlighting the need to further strengthen both awareness and practical skills in radiation safety. The higher proportion of students achieving good knowledge and practice suggests that the current training program has yielded certain positive effects, particularly in providing foundational knowledge on radiation safety.